Value Associations Modulate Visual Attention and Response Selection - Walle, Annabelle; Hübner, Ronald; Druey, Michel D. (Frontiers in Psychology, 2021)
Every day we are confronted with a vast amount of information that all competes for our attention. Some of this information might be associated with rewards (e.g., gambling) or losses (e.g., insurances). To what extent such information, even if irrelevant for our current task, not only attracts attention but also affects our actions is still a topic under examination. To address this issue, we applied a new experimental paradigm that combines visual search and a spatial compatibility task. Although colored stimuli did not modulate the spatial compatibility effect more than gray stimuli, we found clear evidence that reward and loss associations attenuated this effect, presumably by affecting attention and response selection. Moreover, there are hints that differences in these associations are also reflected in a modulation of the spatial compatibility effect. We discuss theoretical implications of our results with respect to the influences of color, reward, and loss association on selective attention and response selection.